Investigation on the Extensibility of the Wood Cell-Wall Composite by an Approach Based on Homogenisation and Uncertainty Analysis - Saavedra-Flores, E (Elsevier Ltd, 2014)
This paper investigates the extensibility of the wood cell-wall composite in the presence of parametric uncertainty by means of a multi-scale finite element approach. Normally, the three fundamental phases in wood, that is, cellulose, lignin and hemicellulose, present considerable scatter in their microstructure and mechanical properties. Nevertheless, by considering uncertainty in their properties, a significant computational cost is added to the solution of a large set of realisations represented by expensive fully-coupled multi-scale analyses. In order to tackle this high cost, we build a statistical approximation to the output of the computer model. Following this strategy, several micromechanical parameters are perturbed to study their influence on the extensibility of the material under tensile loading conditions. By reducing the cost of performing uncertainty analysis of the homogenised mechanical response, we are able to estimate the 5-th, 50-th, and 95-th percentile of the ultimate tensile strains of the material. We contrast our numerical predictions with experimental data, finding a good agreement for a wide range of initial microfibril angles. © 2013 Elsevier Ltd.